Infants Consider the Distributor’s Intentions in Resource Allocation - Strid, Karin; Meristo, Marek (Frontiers in Psychology, 2020)
Recent experimental studies suggest that preverbal infants are able to evaluate agents on the basis of their distributive actions. Here we asked whether such evaluations are based on infants’ understanding of the distributor’s intentions, or only the outcome of their actions. Ten-month-old infants observed animated movies of unequal resource allocations by distributors who attempted but failed to distribute resources equally or unequally between two agents. We found that infants attended longer to the test event showing a third agent approaching a distributor who was unable to make an unequal distribution, compared to the test event where a third agent approached a distributor who was unable to make an equal distribution of resources. Our results suggest that infants’ ability to encode distributive actions goes beyond an analysis of the outcome of these actions, by including the intentions of the distributors whose actions lead to these outcomes.